2019
DOI: 10.3390/nu11010134
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Lutein + Zeaxanthin Presence in Human Placenta and Correlations with Blood Levels and Maternal Dietary Intake

Abstract: Lutein + zeaxanthin (L + Z) are carotenoids recognized in eye health, but less is known about their status during pregnancy. While quantified in maternal and umbilical cord blood, they have never been analyzed in placenta. The purpose of this study is to quantify combined L + Z concentrations in human placenta and correlate with levels in maternal dietary intake, maternal serum, and umbilical cord blood. The proportions of combined L + Z were compared within diet, placenta, maternal serum, and umbilical cord b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Lutein has also been found to be present at higher amounts in cord blood compared to other carotenoids [16,20,21]. Additionally, of the carotenoids present in the placenta, lutein and zeaxanthin were the most prevalent and levels were significantly correlated with levels in maternal serum and infant cord blood [22]. Placenta and umbilical cord blood rely on the mother's dietary intake, thereby reemphasizing the importance of maternal nutrition during pregnancy.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Lutein has also been found to be present at higher amounts in cord blood compared to other carotenoids [16,20,21]. Additionally, of the carotenoids present in the placenta, lutein and zeaxanthin were the most prevalent and levels were significantly correlated with levels in maternal serum and infant cord blood [22]. Placenta and umbilical cord blood rely on the mother's dietary intake, thereby reemphasizing the importance of maternal nutrition during pregnancy.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Table 2 shows the dietary intake of provitamin A carotenoids compiled from the literature [ 16 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Data are listed by geographical origin and by the subpopulations studied in the original articles when reported by age or sex.…”
Section: Resultsmentioning
confidence: 99%
“…Also, L + Z in the placenta was significantly associated with umbilical cord blood and maternal serum L + Z, but not with maternal dietary intake. Of note, confounders that affect the carotenoid status, such as smoking and BMI, were not reported [ 29 ]. Furthermore, Henriksen et al reported an interesting finding in their comparative study between mother-infant pairs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%